A new species of Polyandrocarpa (Ascidiacea, Styelidae) in the Mediterranean Sea - Monniot, F. (Zootaxa, 2016)
Polyandrocarpa arianae n. sp. was collected repeatedly by trawls deeper than 90m from several parts of the Mediterranean Sea. It is described and compared to the shallow species Polyandrocarpa zorritensis (Van Name, 1931) considered as invasive in the Mediterranean Sea. Among the colonial Styelidae the other species which belong to the same genus differ by the colony and zooid shape, the presence/absence of endocarps and of a caecum in the gut loop and by the location and structure of the polycarps.